Characterization of appendiceal microbiome and appendicoliths in acute appendicitis - Vanhatalo, Sanja (fi=Turun yliopisto|en=University of Turku|, 2025)
Acute appendicitis presents as two different diseases: uncomplicated and complicated acute appendicitis. The majority are uncomplicated, which may be treated with antibiotics instead of surgery and possibly even with symptomatic therapy. Complicated acute appendicitis involves necrosis leading to perforation and either peritonitis or a periappendicular abscess. However, the microbiological differences and the role of appendicoliths, fecal concretions in the appendix, in appendicitis severity remain poorly understood. The first part of the thesis was designing and conducting the Microbiology APPendicitis Acuta (MAPPAC) trial. The second aim was to identify differences in appendiceal microbiota between uncomplicated and complicated acute appendicitis. Third study aimed to revise an appendicolith classification from 1966 and to assess the structural and elemental composition of the appendicolith. Fourth study explored the microbiome composition of appendicoliths to elucidate their formation mechanisms. The prospective MAPPAC trial was conducted involving patients with CT confirmed acute appendicitis. The results showed differing appendiceal microbiomes associated with uncomplicated and complicated acute appendicitis. Appendicolith classification showed that even the softest appendicoliths (class 1) are visible by CT. Further results corroborate earlier observations of a concentrically layered inner structure built around distinguishable core, which was detected in most of the harder appendicoliths (class 2 and 3) and was associated with elemental composition. Appendicolith microbiome, enriched with specific Actinobacteria, suggest their potential roles in appendicolith formation. In conclusion, this thesis bridges some knowledge gaps regarding the role of the appendiceal microbiome and appendicoliths in the severity of acute appendicitis, adding to the understanding of this very common surgical disease.

Umpilisäkkeen mikrobiomin ja appendikoliittien karakterisointi akuutissa umpilisäketulehduksessa Akuutti umpilisäketulehdus esiintyy kahtena eri taudin vaikeusasteena: komplisoitumaton eli lievä ja komplisoitunut eli vaikeampi akuutti umpilisäketulehdus. Valtaosa tapauksista on komplisoitumattomia ja voidaan hoitaa antibiooteilla leikkauksen sijaan, tai mahdollisesti jopa oireenmukaisella hoidolla. Komplisoituneeseen tautimuotoon liittyy nekroosi, perforaatio tai abskessi. Mikrobiologiset tekijät ja umpilisäkkeen ulostekiven eli appendikoliitin rooli eri tautimuotojen synnyssä ovat kuitenkin edelleen huonosti ymmärrettyjä. Tämän tutkimuksen ensimmäinen osatyö oli MAPPAC-tutkimuksen suunnittelu ja toteutus. Toisen osatyön tavoitteena oli tunnistaa eroavaisuuksia umpilisäkkeen mikrobistossa komplisoitumattoman ja komplisoituneen tautimuodon välillä. Kolmas tutkimus pyrki luokittelemaan appendikoliitit päivittämällä aiempaa luokitusta vuodelta 1966 sekä arvioimaan niiden rakennetta ja alkuainekoostumusta. Neljäs tutkimus tarkasteli appendikoliittien mikrobiston koostumusta niiden muodostumismekanismien selvittämiseksi. MAPPAC-tutkimus toteutettiin prospektiivisena kliinisenä tutkimuksena potilailla, joilla oli diagnosoitu akuutti umpilisäketulehdus. Tulokset osoittivat eroja umpilisäkkeen mikrobistossa eri tautimuotojen välillä. Appendikoliittien luokittelu osoitti, että jopa pehmeät (luokka 1) appendikoliitit ovat erotettavissa tietokonetomografiassa. Lisäksi tulokset vahvistivat aiempia havaintoja kerrostuneesta sisärakenteesta, joka rakentuu ytimen ympärille ja oli yleinen kovemmissa appendikoliiteissa (luokat 2 ja 3) sekä liittyi niiden alkuainekoostumukseen. Appendikoliittien mikrobistossa havaittiin rikastuneina tiettyjä Aktinobakteereita, mikä viittaa niiden mahdolliseen rooliin appendikoliittien muodostumisessa. Tämä väitöskirjatyö edistää ymmärrystä akuutin umpilisäketulehduksen tautimuotojen välisistä eroista liittyen umpilisäkkeen mikrobistokoostumukseen ja appendikoliitteihin.